Pembangunan Sistem Pengelolaan Event Atma Jaya Yogyakarta Menggunakan React dan .Net5 Berbasis Web dan Mobile - Yohanes Yobel Yuantomo; Yonathan Dri Handarkho; Paulus Mudjihartono (Journal on Education, 2024)
Atma Jaya Yogyakarta University until today, has had its own system to disseminate information to its students and staff, but in terms of event management, the system owned has not met the most important needs of its users. The purpose of this research is to design and build a web and mobile-based event management system using the ASP .Net Core 5 framework and the React Native framework so that it can be used in the Atma Jaya Yogyakarta University environment. The research was conducted through several methods, namely observation, literature study, and system development. In addition, application testing was carried out by distributing questionnaires to 29 respondents who participated on the participant page and 4 respondents on the admin page. After going through the process of designing, building, and testing applications, this research succeeded in building an event management application at Atma Jaya Yogyakarta University with the name UAJY Events. With the construction of the UAJY Events application, management, registration and search for events organized in the university environment can be done more efficiently.